2019
DOI: 10.3855/jidc.11107
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Salmonella spp. in poultry slaughterhouses of southern Brazil

Abstract: Introduction: Salmonella is a major cause of foodborne illness throughout the world. The use of quantitative techniques is important for assessing the risk and determining the capacity of each step of the slaughtering process to decrease or increase bacterial contamination. We aimed to detect and to quantify the presence of Salmonella in Brazilian processing plants by real-time quantitative polymerase chain reaction (qPCR). Methodology: A total of 139 poultry slaughterhouses samples were collected in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Previous studies have already demonstrated that PCR methods can be used to detect foodborne pathogens in chicken and other poultry samples (Alonso et al, 2011;Park et al, 2014). However, they have been carried out only after bacterial preenrichment and/or isolation (Borges et al, 2019;Souza et al, 2019;Borges et al, 2020). The present study demonstrated that Salmonella, Campylobacter, and C. perfringens can be detected directly from broilers' cecal samples obtained in slaughter houses.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Previous studies have already demonstrated that PCR methods can be used to detect foodborne pathogens in chicken and other poultry samples (Alonso et al, 2011;Park et al, 2014). However, they have been carried out only after bacterial preenrichment and/or isolation (Borges et al, 2019;Souza et al, 2019;Borges et al, 2020). The present study demonstrated that Salmonella, Campylobacter, and C. perfringens can be detected directly from broilers' cecal samples obtained in slaughter houses.…”
Section: Discussionmentioning
confidence: 51%
“…Bacterial loads were estimated in all positive samples and the results ranged from 2.8 log 10 to 6.4 log 10, with a mean of 4.3 log 10 bacteria/g of cecal content. This result could be compared to another Brazilian study that presented Salmonella loads ranging from 1.16 to 3.64 log 10 CFU/mL in chicken carcasses (Borges et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, these genes are considered from community origin, and are common in hospital environments (SUN et al, 2013). Thus, the dissemination of resistant strains points out the importance of the Salmonella spp control in poultry meat (BORGES et al, 2019;SIVASANKAR et al, 2020).…”
Section: Discussionmentioning
confidence: 99%